2011
DOI: 10.1007/s12524-011-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Satellite Data in Mapping Salt-Affected Soils Using Linear Spectral Unmixing Analysis

Abstract: Development of salt-affected soils in the irrigated lands of arid and semi-arid region is major cause of land degradation. Hyperion hyperspectral remote sensing data (EO-1) was used in the present study for characterization and mapping of salt-affected soils in a part of irrigation command area of IndoGangetic alluvial plains. Linear spectral mixture analysis approach was used to map various categories of salt affected soils represented by spectral endmembers of slightly, moderately and highly salt-affected so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…The RMSE image shows that the overall pan surface is well explained with the linear mixture of the four selected endmembers except for higher RMSE areas at: (1) the northeast corner and western pan border associated with heavy cattle disturbances; (2) the mainly diagonal SW-NE lines crossing the pan, which are used as driving shortcuts across the pan during the dry season as well as cattle path ways; and (3) the parallel, vertical stripes (~11 • ), associated with remaining sensor noise that were not removed through the pre-processing procedure. In general the performance of the unmixing model is very good with an overall mean RMSE of~1% comparable to equivalent studies, e.g., [105] achieved an mean RMSE of~2% using linear unmixing on Hyperion data to map salt effect soils or [106] getting the same accuracy range for the abundances of vegetation, soil and limestone bedrock. The SMA mapping shows that more than half of the pan surface is dominated by halite crust in variable amounts (Figure 5a).…”
Section: Eo-1 Hyperion Analysessupporting
confidence: 62%
“…The RMSE image shows that the overall pan surface is well explained with the linear mixture of the four selected endmembers except for higher RMSE areas at: (1) the northeast corner and western pan border associated with heavy cattle disturbances; (2) the mainly diagonal SW-NE lines crossing the pan, which are used as driving shortcuts across the pan during the dry season as well as cattle path ways; and (3) the parallel, vertical stripes (~11 • ), associated with remaining sensor noise that were not removed through the pre-processing procedure. In general the performance of the unmixing model is very good with an overall mean RMSE of~1% comparable to equivalent studies, e.g., [105] achieved an mean RMSE of~2% using linear unmixing on Hyperion data to map salt effect soils or [106] getting the same accuracy range for the abundances of vegetation, soil and limestone bedrock. The SMA mapping shows that more than half of the pan surface is dominated by halite crust in variable amounts (Figure 5a).…”
Section: Eo-1 Hyperion Analysessupporting
confidence: 62%
“…Several studies have shown the visible, near infrared, or short-wave infrared spectral bands from the optical sensors to be promising for the detection of surface soil salinity [11][12][13][14][15]. In addition, hyperspectral data have been successfully used in several studies on soil salinity, enabling quantitative assessment of salt-affected soils [16][17][18][19][20][21][22]. However, practical limitations associated with hyperspectral imagery, including the availability of orbital data and the limited spatial coverage of the existing satellite sensors, still limit its potential for regional monitoring of salt-affected soils [23].…”
Section: Introductionmentioning
confidence: 99%
“…Mining interests have been investigated with Magendran and Sanjeevi 11 classifying iron ore and Hosseinjani Zadeh et al 12 mapping a porphyry copper belt. Ghosh et al 13 utilised Hyperion imagery to characterise and map salinated soil in the Indo-Gangetic plains in India. Minimum Noise Fraction (MNF) transformations and Pixel Purity Index (PPI) analysis techniques were combined with linear spectral unmixing to quantify the severity of the salination in the regions examined.…”
Section: Introductionmentioning
confidence: 99%